The role of the school nurse in tackling serious youth violence: an analysis of healthcare provision. (2nd February 2021) - Stephens, Amy; Sayer, Lynn
Abstract : Background: Incidents of serious youth violence have increased; however, the effectiveness of school nurse interventions in reducing these incidents lacks evidence. Aim: To better understand the current role of the school nurse in relation to serious youth violence. Methods: A mixed-method approach was taken, involving two key elements: a staff survey exploring school nurse experiences, interventions and confidence in delivering serious youth violence education and identifying vulnerable children and young people, and an audit of emergency department referrals and school nurse responses. Results: The survey provided no evidence of interventions to reduce serious youth violence. Staff recognised their role in educating children and young people but lacked confidence and wanted further support. School nurse work with children and young people where serious youth violence had been identified mainly involved safeguarding. Only nine of the 62 emergency department referrals were followed up with a face-to-face contact. Conclusion: School nurses recognise their role in serious youth violence but are not reflecting this in practice. Change is required to fulfil their public health role in helping to prevent or reduce serious youth violence.